2015
DOI: 10.3897/zookeys.513.10066
|View full text |Cite
|
Sign up to set email alerts
|

New records of Limoniidae and Pediciidae (Diptera) from Croatia

Abstract: New records are provided for Limoniidae and Pediciidae from Croatia, with new distribution records for species in 12 different genera. Four genera and 18 species are newly recorded for Croatia. Until now, including this data, 87 Limoniidae and eight Pediciidae have been recorded from Croatia. In this paper we confirm presence of Ormosia (Oreophila) bergrothi (Strobl, 1895) and we give the first records of Dicranota (Paradicranota) pavida (Haliday, 1833) and Molophilus (Molophilus) repentinus Starý, 1971 from B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Remarks. Mentioned as Dicranomyia (Dicranomyia) mitis (Meigen, 1830) complex by Kolcsár et al (2015). After re-identification of specimens by Kolcsár L.-P., using the identification key published by Starý and Stubbs (2015), it was confirmed that the specimens belong to Dicranomyia 8 (Kolcsár et al 2015).…”
Section: Hemerodromia Melangynamentioning
confidence: 94%
See 3 more Smart Citations
“…Remarks. Mentioned as Dicranomyia (Dicranomyia) mitis (Meigen, 1830) complex by Kolcsár et al (2015). After re-identification of specimens by Kolcsár L.-P., using the identification key published by Starý and Stubbs (2015), it was confirmed that the specimens belong to Dicranomyia 8 (Kolcsár et al 2015).…”
Section: Hemerodromia Melangynamentioning
confidence: 94%
“…(Ivković et al 2010(Ivković et al , 2012a • Korana Village, Plitvice Lakes NP (25) (Horvat 1990, Ivković et al 2010, 2012a. (Kolcsár et al 2015).…”
Section: Hemerodromia Laudatoria Collin 1927mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there are many new described species in the last decade, especially regarding Diptera (e.g., Ivković et al 2012 ; Kvifte et al 2013 ; Pont and Ivković 2013 ; Andersen et al 2016 ; Kvifte and Ivković 2018 ). For craneflies, the following publications have dealt with the Western Balkans fauna in the last decade: Bilalli et al (2021) , de Jong et al (2021) , Kolcsár et al (2015a , b , 2017a , b , 2018a , b , 2023 ), Keresztes et al (2018a , b ), and Starý (2012) .…”
Section: Introductionmentioning
confidence: 99%